Comparison between standard Vs. Escalated dose venous thromboembolism (VTE) prophylaxis in critically ill patients with COVID-19: A two centers, observational study - Ohoud Aljuhani; Khalid Al Sulaiman; Awatif Hafiz; Khalid Eljaaly; Aisha Alharbi; Rahmah Algarni; Sarah Al Homaid; Khawla Kahtani; Tareq Alsulaiman; Ramesh Vishwakarma; Ghassan Al Ghamdi; Mai Alalawi; et al. (Elsevier, 2022)
Introduction: The risk of mortality in patients with COVID-19 was found to be significantly higher in patients who experienced thromboembolic events. Thus, several guidelines recommend using prophylactic anticoagulants in all COVID-19 hospitalized patients. However, there is uncertainty about the appropriate dosing regimen and safety of anticoagulation in critically ill patients with COVID-19. Thus, this study aims to compare the effectiveness and safety of standard versus escalated dose pharmacological venous thromboembolism (VTE) prophylaxis in critically ill patients with COVID-19. Methods: A two-center retrospective cohort study including critically ill patients aged ≥ 18-years with confirmed COVID-19 admitted to the intensive care unit (ICU) at two tertiary hospitals in Saudi Arabia from March 1st, 2020, until January 31st, 2021. Patients who received either Enoxaparin 40 mg daily or Unfractionated heparin 5000 Units three times daily were grouped under the "standard dose VTE prophylaxis and patients who received higher than the standard dose but not as treatment dose were grouped under "escalated VTE prophylaxis dose". The primary outcome was the occurance of thrombotic events, and the secondary outcomes were bleeding, mortality, and other ICU-related complications. Results: A total of 758 patients were screened; 565 patients were included in the study. We matched 352 patients using propensity score matching (1:1). In patients who received escalated dose pharmacological VTE prophylaxis, any case of thrombosis and VTE were similar between the two groups (OR 1.22;95 %CI 0.52-2.86; P = 0.64 and OR 0.75; 95% CI 0.16-3.38; P = 0.70 respectively). However, the odds of minor bleeding was higher in patients who received escalated VTE prophylaxis dose (OR 3.39; 95% CI 1.08-10.61; P = 0.04). There was no difference in the 30-day mortality nor in-hospital mortality between the two groups (HR 1.17;95 %CI0.79-1.73; P = 0.43 and HR 1.08;95 %CI 0.76-1.53; P = 0.83, respectively). Conclusion: Escalated-dose pharmacological VTE prophylaxis in critically ill patients with COVID-19 was not associated with thrombosis, or mortality benefits but led to an increased risk of minor bleeding. This study supports previous evidence regarding the optimal dosing VTE pharmacological prophylaxis regimen for critically ill patients with COVID-19.